Investigation of the effective mass of electrons in solid solutions Hg₁₋x₋y₋zAxByCzTe - Ostapov, S.E.; Zhikharevich, V.V.; Deibuk, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
This paper presents theoretical investigation on the influence of manganese and zinc in solid solutions of Hg₁₋x₋y₋zAxByCzTe on changes in the electron effective mass.